Port site metastases from previously undiagnosed gastric cancer after laparoscopic cholecystectomy - Bobrzyński, Andrzej; Wysocki, Andrzej; Lejman, Władysław (Contemporary Oncology/Współczesna Onkologia, 2000)
Rare case of port site metastases (PSM) is presented. It concernes a 69 year old man in whom laparoscopic cholecystectomy had been performed 5 months earlier. In 1961 he experienced gastric resection done for ulcer disease. At admission besides PSM he had palpable hard, painless mass in epigastrium. Gastroscopic examination showed normal state, however specimens obtained from gastrojejunostomy revealed cancer tissue.